2015
DOI: 10.1177/0957650915601927
|View full text |Cite
|
Sign up to set email alerts
|

Novel structured dynamic mesh generation for CFD analysis of scroll compressors

Abstract: In order to improve the simulation accuracy of scroll compressors, a novel mesh-generation method of structured dynamic mesh (SDM) is proposed for fluid domains of scroll compressors in this paper. High-quality and density meshes are generated using the SDM in the fluid domains, especially in the flank meshing clearance between wrap profiles in the orbiting and fixed scrolls. The mesh generation process is presented, including scroll solid boundary of fluid domains, structured mesh dividing method in normal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The dynamic mesh technology provided by ANSYS FLUENT [32] was employed to generate the eccentric movement of the orbiting scroll relative to the fixed scroll while changing the enclosed working chamber volumes over time. The dynamic mesh is the most common approach to capture the fluid motion in the complex scroll expander geometry and to reproduce the eccentric movement of the orbiting scroll by means of user-defined functions [12,24,[26][27][28]33,34]. The smoothing and remeshing dynamic mesh schemes were combined and enabled in order to regenerate and recalculate the deforming and moving mesh in the expander working chambers at each time step.…”
Section: Grid Generationmentioning
confidence: 99%
“…The dynamic mesh technology provided by ANSYS FLUENT [32] was employed to generate the eccentric movement of the orbiting scroll relative to the fixed scroll while changing the enclosed working chamber volumes over time. The dynamic mesh is the most common approach to capture the fluid motion in the complex scroll expander geometry and to reproduce the eccentric movement of the orbiting scroll by means of user-defined functions [12,24,[26][27][28]33,34]. The smoothing and remeshing dynamic mesh schemes were combined and enabled in order to regenerate and recalculate the deforming and moving mesh in the expander working chambers at each time step.…”
Section: Grid Generationmentioning
confidence: 99%
“…Two-(2D) and three-dimensional (3D) computational grid approaches to discretise the scroll domain along with the application of different moving mesh methods, to update the deforming mesh over time, can be found in the literature [8][9][10][11][12][13][14][15]. According to Morini et al (2015) [6], a 2D CFD approach is sufficient to evaluate pressure fluctuations in the suction and discharge region in addition to mass flow rate profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Both, structured and unstructured grids have been used for the discretisation of the computational domain of scroll expander geometries [8][9][10][11][12][13][14][15]. It is claimed that CFD simulations on a structured grid are more accurate and reach a converged solution more easily and much faster.…”
Section: Introductionmentioning
confidence: 99%
“…The working chamber of the compressor is closed, so it cannot be studied by direct measurement. Therefore, the fluid working medium in its working chamber can be analyzed by CFD methods [12,13]. Ooi et al [14] used the CFD method to analyze the two-dimensional non-steady-state numerical simulation of the scroll compressor, and found that the heat transfer and leakage between the working chambers have an impact on the fluid distribution in the working chamber, and that the pressure of the distribution has the least impact in the chamber.…”
Section: Introductionmentioning
confidence: 99%